المؤسسات الصغيرة والمتوسطة كآلية لتوفير مناصب الشغل للشباب - عين سوية، ليليا Ain Suweyah, Lailia (قارة وليد, 2019)
يعالج هذا المقال مساهمة المؤسسات الصغيرة والمتوسطة في توفير مناصب الشغل في المجتمع، باعتبار أن هذا النوع من المؤسسات له دور كبير في توفير الاقتصاد للعديد من الدول المتقدمة سواء من ناحية توفير مناصب الشغل أو الحد من مشكلة البطالة. وعليه سوف نسلط الضوء في هذا المقال على دور المؤسسات الصغيرة والمتوسطة في الاقتصاد والتعرف على البرامج التي تساهم في توفير مناصب الشغل للشباب في المجتمع. This thesis treats the involvement of small companies and medium ones in providing job posts in society; since this kind of companies have a big and important role in developing economy in many developed countries wether by providing job posts or by eradicating jobless problems. That is why; in this thesis; we will highlight the role of both; small and medium companies in economy; as well as exploring the programs that help in providing job posts for youth in society.
Keywords: التنمية الاقتصادية -- التنمية الاجتماعية -- سياسات التشغيل -- الجزائر